The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1159/000136384
|View full text |Cite
|
Sign up to set email alerts
|

Caseinophosphopeptide-Bound Iron: Protective Effect against Gut Peroxidation

Abstract: Background: Peptides derived from cow’s milk proteins have in vitro protective effects on iron-induced peroxidation that could be used to prevent the side effects of iron fortification. The aim of the study was to confirm these properties in an in vivo model of gut peroxidation. Methods: Iron bound to the 1–25 phosphopeptide of β-casein [Fe-β-CPP(1–25)] was compared to an encapsulated ferric pyrophosphate (Fe-P) in the Caco-2 model. Ferrous sulfate (FeSO4) was used as control (100 µmol/l iron, n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…According to this, a decrease in MDA production due to the addition of certain PPP fractions prior to treatment with H 2 O 2 in Caco-2 cells has been attributed to the presence of phosphorus in these fractions (Katayama et al, 2006). This protection against lipid peroxidation in H 2 O 2 -induced oxidative stress in Caco-2 cells by a pool of CPPs (to our knowledge reported here for the first time) is in agreement with the results reported by Kibangou et al (2008) using a specific CPP (b-CN(1-25)) bound to iron in Caco-2 cells without induced stress. These authors showed that the complex between b-CN(1-25) and iron decreased or maintained the MDA levels versus iron sulphate or the control, respectively, suggesting a protective effect of this complex against iron-induced peroxidation.…”
Section: Samplesupporting
confidence: 92%
See 1 more Smart Citation
“…According to this, a decrease in MDA production due to the addition of certain PPP fractions prior to treatment with H 2 O 2 in Caco-2 cells has been attributed to the presence of phosphorus in these fractions (Katayama et al, 2006). This protection against lipid peroxidation in H 2 O 2 -induced oxidative stress in Caco-2 cells by a pool of CPPs (to our knowledge reported here for the first time) is in agreement with the results reported by Kibangou et al (2008) using a specific CPP (b-CN(1-25)) bound to iron in Caco-2 cells without induced stress. These authors showed that the complex between b-CN(1-25) and iron decreased or maintained the MDA levels versus iron sulphate or the control, respectively, suggesting a protective effect of this complex against iron-induced peroxidation.…”
Section: Samplesupporting
confidence: 92%
“…In this sense, Katayama, Xu, Fan, and Mine (2006) and Katayama, Ishikawa, Fan, and Mine (2007) have reported that oligophosphopeptides derived from hen egg yolk exert an antioxidant effect against H 2 O 2 , diminishing lipid peroxidation and interleukin-8 secretion, and causing the up-regulation of glutathione (GSH) induced biosynthesis, accompanied by an increase in glutathione reductase (GSH-Rd) and c-glutamylcysteine synthetase activity (c-GCS), as well as the induction of glutathione-S-transferase (GST) and catalase (CAT). To our knowledge, the antioxidant and cytomodulatory activity of CPPs has been previously reported in Caco-2 cells by Kibangou et al (2008); Laparra, Alegría, Barberá, and Farré (2008). The former authors studied the effect of a specific CPP (b-CN(1-25)) against lipid peroxidation, while the latter authors evaluated the effect of a pool of CPPs at 1.4 mg/ml (obtained by simulated gastrointestinal digestion) in comparison to fruit beverages with/without milk, against H 2 O 2 -induced oxidative stress, and reported a potential cytoprotective effect by preserving cell cycle distribution and GSH-Rd induction.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, Kibangou et al . () discovered that the transport of iron bound to β‐CN(1–25) was higher than in the case of iron sulphate or iron pyrophosphate. Besides, they also reported a decrease in iron retention.…”
Section: Resultsmentioning
confidence: 99%
“…Wortley et al (2005) reported that in Caco-2 cell model, the addition of milk increased iron availability from ferric sulphate fortified cereal and indicated that the milk proteins perhaps prevent some of the binding of iron to iron absorption inhibitors such as phytates and phenolics. Similarly, Kibangou et al (2008) discovered that the transport of iron bound to b-CN(1-25) was higher than in the case of iron sulphate or iron pyrophosphate. Besides, they also reported a decrease in iron retention.…”
Section: Influences Of Gpagphgppg On Iron Transport In Caco-2 Cellmentioning
confidence: 99%
See 1 more Smart Citation